A atividade do British Council na area de aperfeiçoamento educacional no que se refere a treinamento de brasileiros na Grã-Bretanha e subsequente avaliação de resultados: um estudo de caso - Guia, Julio Sergio dos Mares (1995)
This case study aims to examine the activities of the British Council in the field of cultural interchange to brazilians as well as to evaluate training programes results carried out in the leveis of reaction, job perfonnance appraisal and organizational under Anthony Hamblin's theory.